Attitudes as correlates to the support of hetorosexuals towards LGBT in the Philippines - Inocencio, Clarice R. 4 0 16; 5 (2019)
ABSTRACT: Homosexuality in the Philippines is widely increasing; however, despite the fact that it is growing some individuals still find it as a problem. Although, Philippines was listed to be one of the gay-friendly countries in Asia and globally, attitudes towards lesbian and gay men and their support to human rights is still unclear. In this study, the researcher measured the attitudes of heterosexuals in the Philippines and their support in the human rights of the LGBT, and also measured the relationship between the attitudes and support to lesbian and gay human rights using a sample population of 100 respondents. As the results from the data gathered, it was found that Filipino heterosexuals are more likely to show a neutral attitude and a moderate support to LGBT human rights, It was also found that the attitude of heterosexuals is not correlated with their support to human rights of lesbian and gay men.
Thesis: (B.S. Psychology) - Pamantasan ng Lungsod ng Maynila, 2019.
Keywords: 2 -- 0; 6; 20; 20; 2